Need Help?

  • Notes
  • Comments & Questions

Solve:
$$x_{1}^{\prime \prime}+10 x_{1}-4 x_2=0$$
$$-4 x_{1}+x_{2}^{\prime \prime}+4 x_{2}=0$$
Where $$x_{1}(0)=0, x_{1}^{\prime}(0)=1, x_{2}(0)=0, x_{2}^{\prime}(0)=-1$$

Applying Laplace Trasform :

$$\mathcal {L}\left\{x_{1}^{\prime \prime}\right\}+\mathcal {L}\left\{ 10 x_{1}\right\}+\mathcal {L}\left\{-4 x_{2}\right\}=0$$

$$s^{2} x_{1}(s)-s x_{1}(0)-x_{1}^{\prime}(0)+10 x_{1}(s)-4 x_{2}(s)=0$$

$$\mathcal{L}\left\{-4 x_{1}\right\}+\mathcal{L}\left\{x_{2}^{\prime \prime}\right\}+\mathcal{L}\left\{4 x_{2}\right\}=0$$

$$-4 X_{1}(s)+S^{2} X_{2}(S)-S X_{2}(0)-X_{2}^{\prime}(0)+4 X_{2}  (S)=0$$

$$\rightarrow\left[s^{2}+10\right] x_{1}(s)-4 x_{2}(s)=1 \quad * s^{2}+4$$

$$\rightarrow-4 x_{1}(s)+\left[s^{2}+4\right] x_{2}(s)=-1 \quad * 4$$

$$\left[\left(s^{2}+10\right)\left(s^{2}+4\right)\right] x_1(s)-4\left(s^{2}+4\right) x_{2}(s)=s^{2}+4 \cdots (1)$$

$$-16 x_{1}(s)+4\left(s^{2}+4\right) x_{2}(s)=-4 \cdots (2)$$

Adding (1) and (2)

$$\left[\left(s^{2}+10\right)\left(s^{2}+4\right)-16\right] x_{1}(s)=\left(s^{2}+4\right)-4$$

$$\rightarrow x_{1}(s)=\frac{s^{2}}{\left(s^{2}+10\right)\left(s^{2}+4\right)-16} $$

$$x_{1}(s)=\frac{s^{2}}{s^{4}+4 s^{2}+10 s^{2}+40-16}=\frac{s^{2}}{s^{4}+14 s^{2}+24} $$

By using Partial fractions:

$$x_{1}(s)=\frac{-1 / 5}{s^{2}+2}+\frac{6 / 5}{s^{2}+12} $$

$$x_{2}(s)=\frac{-s^{2}+6}{\left(s^{2}+2\right)\left(s^{2}+12\right)}=\frac{-2 / 5}{s^{2}+2}-\frac{3 / 5}{s^{2}+12} $$

Apply laplaes inverse in $$x_{1}(s) \& \ x_{2}(s) :$$

$$x_{1}(t)=\frac{-\sqrt{2}}{10} \sin \sqrt{2} t+\frac{\sqrt{3}}{5} \sin 2 \sqrt{3} t$$

$$x_{2}(t)=\frac{-\sqrt{2}}{5} \sin \sqrt{2} t-\frac{\sqrt{3}}{10} \sin 2 \sqrt{3} t$$

No comments yet

Join the conversation

Join Notatee Today!